Kajian Pemasaran Dan Farmer`S Share Karet Alam Rakyat Di Kecamatan Talang Empat Kabupaten Bengkulu Tengah - Anton Feriady; Elni Mutmainnah; Jon Yawahar (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2024)
The aim of this research is to determine marketing channels and analyze farmer's share of natural rubber in Talang Empat District, Central Bengkulu Regency. The research location was chosen deliberately in Talang Empat District to obtain a representative picture of rubber marketing practices in the area. Sampling was carried out using the Slovin formula for farmers and the snowball sampling method for trader collectors. The research results show that there are three main marketing channels for smallholder natural rubber in Talang Empat District: The first channel consists of Farmers - Village Collecting Traders - District Collecting Traders - Wholesalers - Factories. The second channel consists of Farmers – Village Collectors – Wholesalers – Factories and the third channel consists of Farmers – District Collectors – Wholesalers – Factories. The marketing pattern of community rubber in Talang Empat District, if seen from the operational approach including margin, farmer's share and profit and cost ratio, means that the second channel is relatively more efficient compared to other channels. Keywords: marketing, people's natural rubber, farmer's share